Analysis of state for the stocks of sockeye salmon ((Oncorhynchus nerka) from the Bolshaya River (western Kamchatka) in 1929–2022 - O. M. Zaporozhets; G. V. Zaporozhets (Известия ТИНРО)
The spawning stock of sockeye salmon in the Bolshaya River is evaluated for 1929–2022. Long-term tendencies are determined for their most important biological parameters, in particular, a juvenilization of returning spawners with decreasing of their body size, weight, and fecundity. Possible causes of these processes are considered. Biological indices of the sockeye salmon belonged to different races, ecological forms, ecotypes, and genders are compared statistically for different periods of time, with the frequency analysis. Changes in the size and age structure are revealed — range of the size and age variability has decreased. The age structure in the sea adjacent to the Bolshaya River mouth contradicts the hypothesis of a significant portion of sockeye salmon from Lake Kurilskoye in seine by-catch. The sockeye salmon abundance has changed periodically and recently is at the top of the wave. Compared to the 1929–2000 average, the stock has increased 6–7 times by 2020, and more than tenfold in 2022, whereas the average multiplicity of reproduction has increased 9 times (such a high value is obviously due to underestimation of spawning).